2021
DOI: 10.4236/jdm.2021.114010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Three Glucometer Devices Performance in Comparison with the Cobas Integra 400 Plus Autoanalyzer in Measuring Blood Glucose Levels: A Comparative Cross-Sectional Study

Abstract: Objective: The study aimed to evaluate the performance of the three glucometers compared to standard the laboratory method (Cobas Integra 400 Plus) in measuring blood glucose levels. Patients and Methods: A total of 100 Yemeni diabetic patients were randomly recruited into a comparative crosssectional study. Venous and finger-pricked blood samples were obtained from all participants and used for blood glucose levels measurement following the standard procedures. Results: The mean blood glucose levels for one-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(20 reference statements)
1
0
1
Order By: Relevance
“…Studies in Iran reported the stable mean glucose measurements of ABS1 and ABS2 to be 24.3+/-2.4, and 38.8+/-4.5 with a p-value of 0.003 which was statistically signi cant (11) in which. The ndings from Iranian study together with the study by Dahman et al,(21) in the Yemen populations differ from our current study and its ndings as the other two study were carried on records from already known diabetic patients.…”
Section: Glucose Levels and Recorded Values Different Glucometerscontrasting
confidence: 94%
See 1 more Smart Citation
“…Studies in Iran reported the stable mean glucose measurements of ABS1 and ABS2 to be 24.3+/-2.4, and 38.8+/-4.5 with a p-value of 0.003 which was statistically signi cant (11) in which. The ndings from Iranian study together with the study by Dahman et al,(21) in the Yemen populations differ from our current study and its ndings as the other two study were carried on records from already known diabetic patients.…”
Section: Glucose Levels and Recorded Values Different Glucometerscontrasting
confidence: 94%
“…The ndings of this study show that there is a signi cant difference between the mean readings of the glucometers and the laboratory glucose values, with the Accu Chek, Gluco plus and Gluco navii having a positive signi cant direction, their t-value being +2.56, +2.89, +2.41 respectively, and One Touch Plus and Care sense having a negative direction of their mean differences and their variations. This correlated with the ndings by Dahman et al (21) which showed no signi cant difference in blood glucose levels from glucometers when compared with that of the laboratory average values.…”
Section: Glucose Levels and Recorded Values Different Glucometerssupporting
confidence: 89%